Approximation structures and applications to evolution equations - Adrian Duma; Cristian Vladimirescu (Abstract and Applied Analysis)
We discuss various properties of the nonlinear A-proper operators as well as a generalized Leray-Schauder principle. Also, a method of approximating arbitrary continuous operators by A-proper mappings is described. We construct, via appropriate Browder-Petryshyn approximation schemes, approximative solutions for linear evolution equations in Banach spaces.